2020
DOI: 10.3390/su12083183
|View full text |Cite
|
Sign up to set email alerts
|

Cause-Related Marketing and Purchase Intention toward Team-Licensed Products: Moderating Effects of Sport Consumers’ Altruism

Abstract: Cause-related marketing (CRM) has been a crucial concept of sport marketing literature in the professional sport context. However, there is little evidence available to address the effectiveness of CRM when the levels of sport fans' embedded psychological characteristics helping others are considered. The present study aimed to investigate the influence of sport fans' perceived CRM motive of a sport team on fan attitude and purchase intention for the team-licensed products, and the moderating effects of sport … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…In fact, our study has shown that in the context of CRM campaigns, the geographic scope acts as a situational cue for ethnocentric consumers for domestic country bias. In addition, our study extends current literature on CRM effectiveness, e.g., [20][21][22][23][24]43], by suggesting a new significant factor that can affect the success of CRM campaigns, consumers' ethnocentric identity. This identity should be considered in future studies examining the role of geographic scope on CRM effectiveness.…”
Section: Theoretical Contributionssupporting
confidence: 76%
See 2 more Smart Citations
“…In fact, our study has shown that in the context of CRM campaigns, the geographic scope acts as a situational cue for ethnocentric consumers for domestic country bias. In addition, our study extends current literature on CRM effectiveness, e.g., [20][21][22][23][24]43], by suggesting a new significant factor that can affect the success of CRM campaigns, consumers' ethnocentric identity. This identity should be considered in future studies examining the role of geographic scope on CRM effectiveness.…”
Section: Theoretical Contributionssupporting
confidence: 76%
“…Previous researchers have already identified a large number of factors that can make CRM effective, ranging from organizational characteristics, such as the company's origin [37] or the fit between organizational characteristics and the social cause, i.e., the brandcause fit [38][39][40][41] or consumer characteristics such as moral values and emotions [11,[42][43][44], perceived motive of the brand [11], and trust in CRM campaigns [45], as well as the degree of overlap between consumer's characteristics and the cause (i.e., consumer cause identification) [22]. Finally, many researchers have focused on examining various characteristics of the CRM campaign such as the product type involved in the campaign [46,47] or the donation size [48,49].…”
Section: Determinants Of Crm Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…e aims of various topics, such as foodstuffs, social security, religious movements, and aspirations, have been discussed in previous studies in relation to many specific products and companies. For the majority, a smart diet and high-quality goods are preferable [5]. In studies related to personal aspirations and social norms, regarding social commitments, consumers displayed one-sided perceptions [6].…”
Section: Background Of the Studymentioning
confidence: 99%
“…Meanwhile, Brønn and Vrioni (2001) added to these definitions by proposing that CRM is a communication tactic that can build brand reputation and increase customer loyalty. This premise is supported by Baek et al (2020), McCullough and Trail (2022), and A. C. T. Smith and Skinner (2022) proposed that CRM influenced the sport fans' perceptions of the sport organization. Schyvinck et al (2021b) identified two types of networks that are created through CRM relationships namely, "integrative" CRM networks, and "altruistic" CRM networks.…”
Section: Understanding Sport Marketingmentioning
confidence: 85%